Potencial de produção de biogás em escala de bancada de resíduos flotados do abate e processamento de suínos - Abilhôa, Hélen Caroline Zonta (2023)
The generation of waste in the agro-industry is a growing environmental problem, and alternatives for disposing of this waste have been widely studied. In view of this, the energetic use of flotation sludge from the effluent treatment stage of pig slaughterhouses has emerged as an option for adding value to this waste because, due to its composition rich in lipids and volatile solids, it can be used as a substrate for anaerobic digestion and biogas production. In this scenario, flotate samples from two industries were characterized for their potential to generate biogas, through the volume of biogas or methane obtained per unit mass of volatile solids consumed. Four start-up experiments of continuously stirred anaerobic reactors fed with flotate were then evaluated in an attempt to reproduce operating conditions that would be applicable at full scale. The two flotate samples showed good potential for biogas production (PBB), with the highest PBB found for the sample from company 2, which obtained 1,110 ± 154 NmL of biogas/gSVad and 65% methane. The results demonstrate the potential, given that the percentage of methane was higher than 65%. For company 1, the PBB was 565 ± 98 NmL of biogas/gSVad and 73% methane. The reactor start-up experiments showed that it is necessary to heat the reactor biomass and use inoculum, as the substrate used proved to have low buffering capacity. Over time, system failures may occur, as an increase in the AI/AP ratio and decreases in pH were observed, as well as an accumulation of Volatile Fatty Acids over the course of the experiment. An increase in the intermediate alkalinity/partial alkalinity (IA/PA) ratio of 1.59 mgHac.mgCaCO3-1 was observed in Experiment 4, with acetic acid accumulating after increasing the volumetric organic load (VOC). The recommended VOC for this type of substrate in CSTR reactors is 1.0 - 1.3 kgSV.mreator-3. In addition, the use of alkalinity supplementation through co-digestion with manure is an efficient alternative for recovering overloaded reactors.